Development and validation of a normal-phase HPTLC method for the simultaneous analysis of Lamivudine and Zidovudine in fixed-dose combination tablets - Palani Venkatesh; Mahesh Daggumati (Elsevier, 2012)
Simultaneous quantification of Lamivudine and Zidovudine in tablets by HPTLC method was developed and validated. The chromatograms were developed using a mobile phase of toluene:ethyl acetate:methanol (4:4:2, v/v/v) on pre-coated plate of silica gel GF aluminum TLC plate and quantified by densitometric absorbance mode at 276Â nm. The Rf values were 0.41Â±0.03 and 0.60Â±0.04 for Lamivudine and Zidovudine, respectively. The linearity of the method was found to be within the concentration range of 50â250Â ng/spot for Lamivudine and for Zidovudine, it was 100â500Â ng/spot. The lower limits of detection and quantification were 2.23Â ng/spot and 7.90Â ng/spot for Lamivudine and 2.90Â ng/spot and 8.85Â ng/spot for Zidovudine. The method was also validated for precision, specificity and recovery. This developed method was used to analyze fixed-dose tablets (Duovir, Cipla Ltd) samples of Lamivudine and Zidovudine. Keywords: Normal-phase HPTLC, Lamivudine, Zidovudine, Methanol